A fiber optic refractive index sensor with a high index ZnO overlay. (8th March 2019) - Khanikar, Tulika; Singh, Vinod Kumar; Sheoran, Jyoti
Abstract: An intrinsic fiber optic sensor is developed by inserting a section of no-core fiber between two multimode fibers and is applied for refractive index sensing. The sensing principle is based on modulation of evanescent waves, and hence intensity of transmitted light. The sensitivity of the sensor is found to increase by coating the sensing region with a thin layer of high index ZnO. The number of ZnO layers is also optimized and a high sensitivity of 804.57%/RIU is obtained for nine layers of ZnO-coated sensor, with a fast response time of 5 s. Apart from high sensitivity and a fast response time, the experimental investigations also indicate that the proposed sensor produces fairly accurate, stable and repeatable results, with negligible cross sensitivity to environmental temperature.